Pipistrellus (Pipistrellus) nathusii Keyserling and Blasius 1839 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pipistrellus (Pipistrellus) nathusii Keyserling and Blasius 1839 Pipistrellus (Pipistrellus) nathusii Keyserling and Blasius 1839, Arch. Naturgesch., 5 (1): 320. Type Locality: Germany, Berlin. Vernacular Names: Nathusius's Pipistrelle. Synonyms: Pipistrellus (Pipistrellus) unicolor Fatio 1905. Distribution: W Europe to Urals and Caucasus, and W Asia Minor; S England. Conservation: IUCN 2003 and IUCN / SSC Action Plan (2001) – Lower Risk (lc). Discussion: Subgenus Pipistrellus . Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 476, DOI: 10.5281/zenodo.7316519